1995
DOI: 10.1080/00140139508925252
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of scanning postures among grocery cashiers and its relationship to checkstand design

Abstract: Mounting evidence suggests that musculoskeletal disorders are prevalent among US retail food workers. Cashiers who use electronic scanners appear to be at especially high risk for upper extremity musculoskeletal disorders. Checkstand design has been implicated as a contributor to musculoskeletal injury among cashiers because workstation design can significantly impact working posture. The present study examines working posture among two groups of cashiers to determine if checkstand design is associated with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Marras et al (1993Marras et al ( , 1994Marras et al ( , 1995, Grant et al (1993), Grant and Habes (1995) and Rodrigues (1989) assessed various checkstand designs by use of instrumentation to quantify joint dynamics, expert evaluation, posture estimation and heuristic analysis. These researchers recommended a frontfacing design (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Marras et al (1993Marras et al ( , 1994Marras et al ( , 1995, Grant et al (1993), Grant and Habes (1995) and Rodrigues (1989) assessed various checkstand designs by use of instrumentation to quantify joint dynamics, expert evaluation, posture estimation and heuristic analysis. These researchers recommended a frontfacing design (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Supermarket cashiers spend most of their work time at a checkout station, thus its design may have some effects on them. The checkout design is important, as it is a potential determinant for the prevalence of MSDs among supermarket cashiers as have been reported [26,29,149,150]. Many studies have been conducted on workstation ergonomics and its effect on the cashiers; however, it is out the scope of this literature review.…”
Section: Cashier Worktation (Checkout) Design and Some Featuresmentioning
confidence: 99%
“…The etiology of MSDs occurrence remains unclear; however, some work-related factors increase the prevalence of MSDs among cashiers [26]. These factors include, (a) performing repetitive upper limb and hand activities [27], (b) working in a static posture [28], (c) performing work at high speed [23] and (d) worker satisfaction and dissatisfaction regarding the job [29].…”
Section: Repetitive Movement and Accumulated Injuries/disorders Among Cashiersmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of supermarket check-out workers, Grant and Habes [44] found awkward postures to be only one of several ergonomic risk factors that may contribute to MSDs. Repetitive handling of merchandise was found to be a substantial source of physical stress to supermarket check-out workers.…”
Section: Supermarket Check-out Workersmentioning
confidence: 99%